KEUANGAN MASJID DAN MODAL SOSIAL - Efi Syarifudin (Al Qalam, 2009)
This article tries to discuss the forms of philantrophy developed by society to meet the need of financial capital and the factors that become the sosial capital as a supporting factor for the smooth-running of the economy of the mosques: The study uses functional-structuralisme approach to explain the local wisdom of Singarajan People located in Subdistrict Pontang in fullfilling the needs of the mosque funding.Collecte (kotak jum'at), mider (monthly obliged payment), endowment (infak), one-tenth wet rice field of the mosque, wakaf (religious foundation), recompens (hasil selawat) used as the financial sources of Masjid Agung Baetut Taqwa become the concrete samples of the local wisdom of philantrophy practices of all financial sources of the mosque, one-tenth wet rice-field of the mosque gives the greatest contribution. The collected fund is used to fund kaom, supplies expense, care and maintenance, and renovation of the mosqueBased on functional-structuralime point of view, the participative and philantrhropical attitudes of Singarajan society are motivated by the strong structure of kindship and are influenced by the socialites and the ulama. Moreover, the mythes or oral stories dealing with the mosque, wakaf, and other property's right of the mosque that are able to prevent moral distrust toward pilanthripical practices become another influencing factor of participative and philantrhropical attitudes.